Integrated approach for exploring critical elements that affect sustainable development of cultural and creative industries - Wu, Yueh-Cheng; Lin, Sheng-Wei (Journal of Business Economics and Management, 2021)
The cultural and creative industries (CCIs) are increasingly regarded as a means to cure economic stagnation and boost sustainable development; thus, they have become the focus of cultural, social, and economic policies. This study adopts a city governance perspective to explore topics that should be considered in CCIs development. We combine entropy weight and grey relational analysis into an evaluation indicator system that considers ambiguity and complexity. The results reveal the cities in the eastern region and offshore islands took more advantage of investment in cultural resources than cities in the western region. It indicates that local governments understand that the economic benefits of culture are not limited to certain CCIs but extend to the overall economy. Through stimulus policies, communities have been built and effectively revitalized regional economies. The developed method prioritizes the provision of cultural and creative resources to effectively improve resource–generating capacity of a city. This study provides suggestions for decision makers in cultural and creative sectors to help them overcome the gap in resource allocation between urban and rural areas.